Lung and other cancer site mortality in a cohort of Italian cotton mill workers. Issue 10 (16th April 2008) - Mastrangelo, G; Fadda, E; Rylander, R; Milan, G; Fedeli, U; Rossi di Schio, M; Lange, J H
Abstract : Background: Several studies report a lower than expected mortality in lung cancer among workers exposed to organic dust. Recent studies also reported a decreased risk for cancer at other sites. Objectives: To evaluate the mortality from lung and other cancer sites in cotton mill workers. Material and methods: A cohort of 3961 Italian cotton mill workers was divided into those working with carding (exposed to high levels of endotoxin-containing cotton dust) and other tasks, which generally have lower exposure. Standardised mortality ratios (SMRs), with 95% confidence intervals (CI), were calculated using death rates of the regional general population as a reference. Cancer mortality was analysed in relation to the length of employment in the two task groups. An internal analysis was also performed through Poisson regression. Results: Among workers in carding departments, lung cancer SMRs were 1.88 (CI: 0.69 to 4.08), 1.01 (CI: 0.20 to 2.94) and 0.22 (CI: 0.00 to 1.24), respectively, for <6, 6–12 and >12 years of employment (χ 2 for trend = 5.45; p<0.05). A significant (p = 0.04) trend was confirmed by Poisson regression. No reduced risks were found for other forms of cancer, nor for those working with other tasks. Conclusions: The results support previous reports that a high and prolonged exposure to cotton dust and other endotoxin-containing organic dusts is related to a lower risk of lung cancer. There was no indication of a reduced risk for other forms of cancer.